ANALYSIS OF COORDINATE-BASED ACCOUNTING INFORMATION SYSTEM EFFECTIVENESS FOR OIL PALM PLANTATION - admin, Benedictus Prabani Indrawahyu Darpito B42112005 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this research is to understand the consequence of internal control implementation in the palm oil plantation that will affected the effectiveness of the budget allocated and invested to the palm oil plantation of PT Sawit Jaya Makmur. The research was made to examine the effectiveness of budget realization of the company in related with the current internal control and the projection of the budget realization effectiveness if the company using Coordinate-Based Accounting Information System implemented in the plantation area. The method used in this research is qualitative method with technique of data collection done by interview, documentary study, and field research in the plantation area of PT Sawit Jaya Makmur.The study result show that there is inefficiency in the budget realization due to lack of internal control in the field. In the other hand, PT Sawit Jaya Makmur had realized the budget realization inefficiency issue and put an effort to create and design better internal control system to minimize the inefficiency of budget realization in the field. From the research can be concluded that PT Sawit Jaya Makmur should improve the internal control system to minimize inefficiency and loses and should be able to implemented the new internal control system to reach maximum budget realization efficiency. Keywords: internal control, budget realization, effectiveness of realization.